Effect of Lower Body Compression Garments on Hemodynamics in Response to Running Session - Tomas Venckūnas; Eugenijus Trinkūnas; Sigitas Kamandulis; Jonas Poderys; Albinas Grūnovas; Marius Brazaitis (The Scientific World Journal)
Purpose. Compression garments are often worn during exercise and allegedly have ergogenic and/or physiological effects. In this study, we compared hemodynamics and running performance while wearing compression and loose-fit breeches. We hypothesized that in neutral-warm environment compression breeches impair performance by diminishing body cooling via evaporative sweat loss and redistributing blood from active musculature to skin leading to a larger rise in body temperature and prolonging recovery of hemodynamics after exercise. Methods. Changes in hemodynamics (leg blood flow, heart rate, and blood pressure during orthoclinostatic test), calf muscle tissue oxygenation, and skin and core temperatures were measured in response to 30 min running (simulation of aerobic training session) followed by maximal 400 m sprint (evaluation of running performance) in recreationally active females (25.1±4.2 yrs; 63.0±8.6 kg) wearing compression or loose-fit breeches in randomized fashion. Results. Wearing compression breeches resulted in larger skin temperature rise under the garment during exercise and recovery (by about 1°C, P<0.05; statistical power > 85%), while core temperature dynamics and other measured parameters including circulation, running performance, and sensations were similar compared to wearing loose-fit breeches (P>0.05). Conclusion. Compared with loose-fit breeches, compression breeches have neither positive nor negative physiological and performance effects for females running in thermoneutral environment.